MAKNA KONSEPTUAL KATA KERJA DERU DALAM ASAHI SHINBUN EDISI 42435 DAN 42437 - Eko Kurniawan (IZUMI, 2018)
(Title: Conceptual Meaning of Verb Deru in Asahi Shinbun Issue No. 42435 and 42437) This study aims to assess information about the conceptual meaning of verb deru in Asahi Shinbun issue no. 42435 and 42437. Research based on the theory of Kindaichi (1988) for analyzing conceptual meaning of verb deru in many contexts and theory of Bunkacho (1981), Matsuura (1994) for comparing. This is a kind of qualitative research. The method used in this research is the descriptive analysis. Source of data in this study is Asahi Shinbun issue no. 42435 and 42437. While the data in this study are sentences containing verb deru that represent in many contexts. Data collection technique which used is observing method. The results showed, conceptual meaning of verb deru in Asahi Shinbun are based on the theory of Kindaichi (1988) and  theory of Bunkacho (1981), Matsuura (1994) for comparing: go out, give argument, enter, go forward, appear, go to office or attend, published, cause, do, answer telephone, follow, experience, have/has, reported, deported and known. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor